Women, work and industrial relations in Australia in 2021. (June 2022) - Lee, Talara; Good, Laura; Lipton, Briony; Cooper, Rae
The year 2021 has been momentous for women at work in Australia. Two key themes loom large: first, the highly gendered impact of the COVID-19 pandemic on paid and unpaid work, and second, the ongoing crisis of persistent gender-based disrespect and violence in Australian workplaces. Both have prompted escalating demands for change to provide women with better jobs, improve the balance between work and care, and ensure more respect at work. This article examines these issues, briefly analyses the 2021–22 Federal Budget and parental leave policy in Australia a decade after a national scheme commenced, and foreshadows several issues on women and work to watch in 2022.